Catalytic and molecular insights of the esterification of ibuprofen and ketoprofen with glycerol - Toledo, Victoria (2021)
The esterification of rac-ibuprofen and rac-ketoprofen with glycerol catalyzed with the commercial biocatalyst Novozym® 435 was investigated at 45 °C with various profen: glycerol molar ratios using 2-propanol as co-solvent in a batch type reaction. The conversion of rac-ibuprofen reached 46%, with an enantiomeric excess towards the S-enantiomer of 42%. When 1:4 ibuprofen:glycerol molar ratio was assayed, 75% of the R-ibuprofen reacted with glycerol towards the monoglyceride with 99% selectivity, which is highly relevant in the field of prodrugs synthesis. The conversion of rac-ketoprofen was lower, 17 % vs. 46 % of rac-ibuprofen, and the esterification afforded both the monoglyceride (70%) and diglyceride (30%) regardless of the ketoprofen:glycerol molar ratio. Investigations of the esterification at molecular level through concentration-modulated infrared spectroscopy, static ATR-FTIR and in situ Raman spectroscopy showed the continuous decay of the species belonging to rac-ibuprofen and glycerol providing further evidences of the reaction. Moreover, the interaction of CALB with ibuprofen modifies the contribution of the ordered structures of the lipase, which might be related with the improved catalytic performance in the esterification of that profen.